ANALYSIS ON STUDENTS’ METAPHOR PARAPHRASE IN THE PICTURE OF DORIAN GRAY - Alawiyah, Utin Novianti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:This study aims to know students? ability in paraphrasing metaphors found in the novel within certain chapter in sixth semester students of English Department Study Program of Tanjungpura University in academic year 2016/2017. The method used is the descriptive qualitative method which is to find deeper understanding toward students? ability in paraphrasing the metaphors. The population of this research is 10 students who produced 100 text of metaphor paraphrase. The result of this study shows that the students used all the procedure except calque. The most used procedures by the students are equivalence procedure with percentage 29% out of 100%. At the end of the research, the researcher found that the students skill in paraphrasing the metaphor were quite good. The students scored above average in total nine of ten students. Thirty three errors found in total consist of fourteen errors in grammar and nineteen errors in paraphrasing. Keywords: Paraphrase, Metaphor, Students? Ability Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan dalam menafsirkan metaphor pada novel dalam bab tertentu oleh mahasiswa semester enam Pendidikan Bahasa Inggris Universitas Tanjungpura tahun ajaran 2016/2017. Metode penelitian yang digunakan adalah deskripsi kualitatif untuk pemahaman lebih dalam terhadap kemampuan siswa menafsirkan metafor. Populasi penelitian ini adalah 10 mahasiswa yang menghasilkan 100 teks tafsiran metafor. Hasil penelitian ini menunjukkan bahwa mahasiswa menggunakan semua prosedur kecuali calque. Prosedur yang paling banyak digunakan adalah prosedur keseimbangan dengan persentase 29% dari 100%. Diakhir penelitian, peneliti menemukan bahwa kemampuan mahasiswa dalam menafsirkan metaphor cukup baik. Mahasiswa memiliki nilai di atas rata-rata dengan total 9 dari 10 orang. Total tiga puluh tiga kesalahan ditemukan terdiri atas empat belas kesalahan di tata bahasa dan sembilan belas kesalahan dalam menafsirkan. Kata Kunci : Tafsiran, Metafor, Kemampuan Mahasiswa